Analysis of Time Acceleration in The Malaka Regent's Office Construction Project Using The Critical Path Method (CPM) and Time-Cost Trade-Off (TCTO) - Thomas Aquino Seki; Laksono Djoko Nugroho; Esti Wulandari (Jurnal Teknik Indonesia, 2026)
The construction of the Malaka Regency Regent's Office has encountered significant challenges, including recurring project delays caused by factors such as design changes, unpredictable weather conditions, labor shortages, and insufficient materials or equipment. These issues have resulted in inefficiencies in project scheduling and cost management, highlighting the need for effective project management strategies. This study aims to analyze the project schedule, identify the critical path, and evaluate schedule acceleration alternatives for the Malaka Regent's Office construction project using the Critical Path Method (CPM) and the Time–Cost Trade-Off (TCTO) method. The study applied the Critical Path Method (CPM) and the Time–Cost Trade-Off (TCTO) method to analyze the project schedule, identify critical activities, and evaluate feasible acceleration strategies. The analysis showed that the originally planned project duration of 224 calendar days could be reduced to 196 calendar days using the CPM approach, while the TCTO method further shortened the project duration to 182 calendar days. This acceleration was achieved by minimizing idle time between critical activities, optimizing resource allocation, and implementing time–cost trade-off strategies without compromising the project's quality or scope. The findings demonstrate the effectiveness of CPM and TCTO in optimizing construction schedules and reducing project delays. Furthermore, this study provides a practical framework for improving schedule and cost performance in construction projects, particularly those involving public infrastructure development.